2016
DOI: 10.1021/acs.chemmater.6b01949
|View full text |Cite
|
Sign up to set email alerts
|

Microporous Organic Polyimides for CO2 and H2O Capture and Separation from CH4 and N2 Mixtures: Interplay between Porosity and Chemical Function

Abstract: Porous polyimides have been considered to be a promising material class for gas capture and sequestration, leading to the synthesis of a substantial number of individual networks with noteworthy sorption properties. In spite of these efforts, the vision of a chemical control of adsorption and desorption of small molecules, in particular, for the competing uptake of technical relevant gas mixtures, is still hardly investigated. Here, we present a systematic study of five new polyimide networks based on a set of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
46
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 58 publications
(159 reference statements)
2
46
0
Order By: Relevance
“…Apart from imine-linked porousn etworks, Senker et al [73] also reported as eries of microporous organic polyimides (Figure 12 a), which incorporatearange of bridging groups including diphenylsulfone (MOPI-I), diphenylether (MOPI-II), benzophenone (MOPI-III), bicycle[2,2,2]oct-7-en (MOPI-IV), and hexafluoro-2,2-diphenylpropane (MOPI-V). All of the water sorption isotherms (Figure 12 b) showedagradual rise throughout the entire relative pressure range,i ndicating that the sorbents contain hydrophilic sites.…”
Section: Water Favorable Popsmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from imine-linked porousn etworks, Senker et al [73] also reported as eries of microporous organic polyimides (Figure 12 a), which incorporatearange of bridging groups including diphenylsulfone (MOPI-I), diphenylether (MOPI-II), benzophenone (MOPI-III), bicycle[2,2,2]oct-7-en (MOPI-IV), and hexafluoro-2,2-diphenylpropane (MOPI-V). All of the water sorption isotherms (Figure 12 b) showedagradual rise throughout the entire relative pressure range,i ndicating that the sorbents contain hydrophilic sites.…”
Section: Water Favorable Popsmentioning
confidence: 99%
“…(b) Adsorption (closed symbols) and desorption isotherms (opensymbols) of water vapor for MOPIs. Reprinted with permission from Ref [73]…”
mentioning
confidence: 99%
“…Gas adsorption is a fundamental unit operation that is important for chemical engineering, greenhouse‐gas capture, and pollution treatment . Both chemical and physical adsorption techniques have been employed in practical applications .…”
Section: Introductionmentioning
confidence: 99%
“…Gas adsorption is af undamental unit operation that is important for chemicale ngineering, greenhouse-gas capture, and pollutiont reatment. [1][2][3] Both chemical andp hysicala dsorption techniques have been employed in practical applications. [4,5] For example, the traditional methodf or fixing CO 2 is to bubble the mixed gases through aqueous alkanolamine.…”
Section: Introductionmentioning
confidence: 99%
“…Covalent-organic frameworks (COFs) have attracted extensive interests in gas separation, [12] electrolyte membrane, [13] and electrochemical devices recently. [14,15] Rational design of COFs is effective to realize their versatile functionalities and applications.B yt uning the functional groups, Jiangsg roup reported aC OF from hexaazatrinaphthalene and diethynylbenzene to deliver acapacity of 147 mAh g À1 .…”
mentioning
confidence: 99%